2018
DOI: 10.1007/s00604-018-2964-6
|View full text |Cite
|
Sign up to set email alerts
|

A polymer monolith incorporating stellate mesoporous silica nanospheres for use in capillary electrochromatography and solid phase microextraction of polycyclic aromatic hydrocarbons and organic small molecules

Abstract: An inorganic-organic hybrid monolith incorporated with stellated mesoporous silica nanoparticles (SMSNs) was prepared. Using binary solvents, deep eutectic solvents and room temperature ionic liquids, an SMSN-incorporated poly(butyl methacrylate-co-ethylene glycol dimethacrylate) monolith demonstrated uniform structure with good column permeability. A systematic investigation of preparation parameter was performed, including SMSN content, crosslinking monomer content, and the component of binary solvent. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Following this new development, Wang et al and Mendonça et al published the first studies on the use of different DES as ligand [77], as 100% solvent for SARA ATPR [78] or both [77]. Other studies also reported the use of DES as solvent medium for polymer synthesis [46,79,80,81,82,83,84,85,86,87,88,89,90]. In particular, the communication of Park and Lee on the polymerization of 3-octylthiophene in DES presented interesting features regarding the use of DES as a solvent in polymerization.…”
Section: Polymeric Synthesis Using Desmentioning
confidence: 99%
“…Following this new development, Wang et al and Mendonça et al published the first studies on the use of different DES as ligand [77], as 100% solvent for SARA ATPR [78] or both [77]. Other studies also reported the use of DES as solvent medium for polymer synthesis [46,79,80,81,82,83,84,85,86,87,88,89,90]. In particular, the communication of Park and Lee on the polymerization of 3-octylthiophene in DES presented interesting features regarding the use of DES as a solvent in polymerization.…”
Section: Polymeric Synthesis Using Desmentioning
confidence: 99%
“…Ionic liquids (ILs) are the organic salts consisted of large asymmetric organic cations and inorganic or organic anions . Because IL could be custom‐made with different functions to meet various requirements and its superior properties such as thermal and chemical stability and good solvent performance , it has been widely used in CEC.…”
Section: Monolithic Capillary Electrochromatographymentioning
confidence: 99%
“…Therefore, it is necessary to reduce their hydrophobicity to improve the analytical performance in aqueous media. In this sense, hydrophilic ILs have attracted significant attention as functional monomer to prepare MIPILs [67][68][69][124][125][126], and as porogen agents to improve the characteristics of the MIPs [66,[127][128][129].…”
Section: Polymer-based Ionic-liquid Composites (Pol-ils)mentioning
confidence: 99%
“…MIPIL-based sorbents have been mainly used for the selective determination of antibiotics [68,69,124], drugs [125], herbicides [126], phenolic acids [67], and phthalate esters [66], among others [127][128][129]; and in different matrixes, such as water [68,69,124,129], soils [68,69,124], and food and drinks [66,67,126].…”
Section: Polymer-based Ionic-liquid Composites (Pol-ils)mentioning
confidence: 99%